Modelling the change in the oxidation coefficient during the aerobic degradation of phenol by acclimated activated sludge - Lobo, Cintia Cecilia (2014)
In this work the aerobic degradation of phenol by acclimated activated sludge was studied. Results demonstrate that while the phenol removal rate by acclimated activated sludge follows the Monod model, the oxygen uptake rate obeys a Haldane-type equation. The phenol oxidation coefficient obtained at different intial phenol concentrations ranged from 1.9 to 2.6 mol O2 · mol-1 phenol. A mathematical model based on a simplified version of the catalytic mechanism of the enzyme phenol 2-monooxygenase was developed to predict transient phenol concentrations and oxygen requirements by phenol-acclimated activated sludge in batch reactors under different initial phenol concentrations. The proposed model not only adequately represents the experimental results of the present paper, but also those reported by other authors. Particular cases of the proposed model are discussed.